2005
DOI: 10.1007/s00192-005-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of transobturator suburethral sling (Monarc) vs suprapubic arc (Sparc) sling procedures for female urodynamic stress incontinence

Abstract: The aims of this trial were to compare the attendant complications and postoperative voiding function of the Monarc and suprapubic arc (Sparc) suburethral sling procedures. This is the first article in English literature to compare different suburethral sling procedures using prosthesis of the same material and the same weave. Sixty women with urodynamic stress incontinence alone or combined with pelvic prolapse less than International Continence Society stage II were randomly allocated to either the Monarc or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 23 publications
2
17
2
2
Order By: Relevance
“…While it was reported that these complications could be seen in TVT procedure with the rate %2-4, no significant hemorragical complication has been reported in TOT operation. It was accepted that TOT procedure could minimize the occurrence of this kind of complications (28,29). It was seen that no major complication related to the TOT operation, such as bladder perforation, bowel perforation, urethral perforation, vessel injury, and obturator hematoma, occurred in our study.…”
Section: Discussionsupporting
confidence: 46%
“…While it was reported that these complications could be seen in TVT procedure with the rate %2-4, no significant hemorragical complication has been reported in TOT operation. It was accepted that TOT procedure could minimize the occurrence of this kind of complications (28,29). It was seen that no major complication related to the TOT operation, such as bladder perforation, bowel perforation, urethral perforation, vessel injury, and obturator hematoma, occurred in our study.…”
Section: Discussionsupporting
confidence: 46%
“…Results show that the success of the operation is comparable with retropubic procedures, but compared to these, the transobturator approach involves far less complications [3,4]. To carry out the operation, a monofilament polypropylene tape is introduced and placed under the urethra by two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005 [11] a prospective randomised trial of 60 patients compared Sparc and Monarc slings, and reported similar success rates at a mean follow up of 9 months.…”
Section: Discussionmentioning
confidence: 95%